Implementation of Program to Increase Men's Participation in the Use of Vasectomy Contraception - Ilham Syahputra; Hidayat Hidayat; Ratih Baiduri (Jurnal Administrasi Publik (Public Administration Journal), 2020)
This study aims to find out how to implement a program to increase the use of vasectomy contraception, to identify the implementation of vasectomy contraceptive services and to know the role and function of stakeholders in the implementation of vasectomy contraceptive use policies. This research was conducted through a qualitative research with a descriptive approach conducted in Tanjung Morawa Sub-District, Deli Serdang Regency. The research informants were determined by purposive sampling technique by involving the Department of Family Planning program manager in Deli Serdang District, family planning counselors, family planning cadres and acceptors (users) of vasectomy contraception. Research data collection were done through interviews, observation and documentation studies. The results indicates that the management of family planning programs was based on the mandate of Law No. 52/2009 where the government through the National Population and Family Planning Agency (BKKBN) carries out the function of controlling population and organizing family planning (KB) programs. In managing the vasectomy family planning program in Tanjung Morawa Sub-district, Deli Serdang Regency, there were several parties that have an important role in disseminating information and facilitating vasectomy services such as the Population Control Office, Family Planning and Women's Empowerment, Deli Serdang Regency Child Protection, Family Planning Extension, Family Planning Motivators and Family Planning Cadres. Strategy of vasectomy service for free, mobile services as well as the provision of incentives for vasectomy acceptors were able to attract menâ€™s interest Â to be involved in family planning programs as users of vasectomy contraception.